Problems affecting young mothers in attending ABET classes in Bohlabela District in the Limpopo Province - Manyike, Norman Msumbuluko (My University, 2007)
This report describes the research carried out in the Limpopo Province of South Africa, with Bohlabela District being used as a site of this study. The aim of the study was to investigate problems affecting young mothers in attending ABET classes in Bohlabela District in Limpopo Province. In order to achieve the aim outlined above, I formulated the following main research question: • What are the problems affecting the attendance of ABET classes by young mothers in Bohlabela District in the Limpopo Province? In trying to answer the question outlined above, I decided to undertake an explorative study in order to investigate problems affecting the attendance of ABET classes by young mothers in Bohlabela District in the Limpopo Province. In chapter 1 I further gave a description of South Africa in the apartheid era and the post-apartheid South Africa in terms of its geographical setup and education. The aim and objectives of the study and the research questions are indicated. The scope of the study is explained. In chapter 2 the theoretical foundation for the investigations of problems affecting the attendance of ABET classes by young mothers in Bohlabela District in the Limpopo Province is indicated. Factors such as time, curriculum, environment, family pressures and ignorance were discussed in this chapter. The chapter is starting with the definition of key concepts. In chapter 3 the research design of the study has been outlined. The data collection paths of the study have been discussed. The chapter explains how the data which had been collected from various places were analysed using qualitative data analysis methods. It concludes by discussing what I call ‘reflections’, a section that was about my main learning experiences and difficulties that I encountered during the process of this research. In chapter 4 I presented the findings of the study according to the views and perceptions of the interviewees. This section prepared the study for the next stage of the investigation where I established whether or not the findings provide answers to the research question. Chapter 5 is the concluding section where conclusions were made based on the findings of the investigation. Recommendations coming out of the study were made and finally recommendations for further study have been outlined.
Thesis (M.ED.) --University of Limpopo, 2007
Keywords: Adult learning; Teenage mothers -- South Africa -- Limpopo; Adult education -- South Africa -- Limpopo